Dual-Acting Cholinesterase-Human Cannabinoid Receptor 2 Ligands Show Pronounced Neuroprotection in Vitro and Overadditive and Disease-Modifying Neuroprotective Effects in Vivo - Scheiner, Matthias; Dolles, Dominik; Gunesch, Sandra; Hoffmann, Matthias; Nabissi, Massimo; Marinelli, Oliviero; Naldi, Marina; Bartolini, Manuela; Petralla, Sabrina; Poeta, Eleonora; Monti, Barbara; Falkeis, Christina; et al. (Journal of Medicinal Chemistry, 2019)
We have designed and synthesized a series of 14 hybrid molecules out of the cholinesterase (ChE) inhibitor tacrine and a benzimidazole-based human cannabinoid receptor subtype 2 (hCB2R) agonist and investigated them in vitro and in vivo. The compounds are potent ChE inhibitors, and for the most promising hybrids, the mechanism of human acetylcholinesterase (hAChE) inhibition as well as their ability to interfere with AChE-induced aggregation of β-amyloid (Aβ), and Aβ self-aggregation was assessed. All hybrids were evaluated for affinity and selectivity for hCB1R and hCB2R. To ensure that the hybrids retained their agonist character, the expression of cAMP-regulated genes was quantified, and potency and efficacy were determined. Additionally, the effects of the hybrids on microglia activation and neuroprotection on HT-22 cells were investigated. The most promising in vitro hybrids showed pronounced neuroprotection in an Alzheimer's mouse model at low dosage (0.1 mg/kg, i.p.), lacking hepatotoxicity even at high dose (3 mg/kg, i.p.).
CRIS-Team Scopus Importer:2019-10-29